E-Mediation Sebagai Langkah Efektif Alternatif Penyelesaian Sengketa Pertanahan Dalam Menyambut Era Society 5.0 - Shara, Made Cinthya Puspita; Martana, Putu Ade Hariesta (Acta Comitas : Jurnal Hukum Kenotariatan, 2024)
The purpose of this paper, as a form of follow-up to the current land digitization plan in Indonesia, and as an effort to formulate an e-mediation policy at the ATR/BPN Institution for alternative dispute resolution in the land sector in Indonesia. This writing uses normative legal research methods based on the regulation of Permen ATR/BPN, and comparative legal studies with China in the application of E-Mediation. The results in this paper, based on the provisions in Supreme Court Regulation Number 1 of 2016 and Supreme Court Regulation Number 3 of 2022, pave the way for the implementation of an electronic mediation dispute resolution system. The design of e-mediation efforts that can be used as a first step in resolving land disputes through the help of Artificial Intelligence (AI) in collaboration with the ATR/BPN. This concept is a follow-up effort to the Electronic Land Certificate policy that was promoted in the Complete Systematic Land Registration (PTSL) Program through the Ministry of ATR/BPN in 2017.